Analysis and design of hybrid systems 2006 : a proceedings volume from the 2nd IFAC Conference, 7-9 June, 2006, Alghero, Italy /: a proceedings volume from the 2nd IFAC Conference, 7-9 June, 2006, Alghero, Italy. (2006) - Unknown
No abstract available